Kiss of the yoginī : "Tantric sex" in its South Asian contexts - White, David Gordon (University of Chicago Press, 2003)
For those who wonder what relation actual Tantric practices bear to the ""Tantric sex"" currently being marketed so successfully in the West, David Gordon White has a simple answer: there is none. Sweeping away centuries of misunderstandings and misrepresentations, White returns to original texts, images, and ritual practices to reconstruct the history of South Asian Tantra from the medieval period to the present day. Kiss of the Yogini focuses on what White identifies as the sole truly distinctive feature of South Asian Tantra: sexualized ritual practices, especially as exp.